Materials-Related Solutions for Industry - Wellmann, Peter (Materials Innovation for the global circular economy and sustainable society, 2017)
The purpose of the Sixth World Materials Summit, as was true of its five predecessors, is to bring together policy- and decision-makers, experts in markets and industrial technologies, and leaders from the science research community. They assess the status of the many global challenges we face today, identify the best paths forward, and recommend actions that will get us moving along those paths. This year’s program focuses on Materials Innovation for the Global Circular Economy and Sustainable Society. The economic model that focuses on eliminating waste and inefficiency and promotes greater resource productivity — what we call the ‘circular economy’—has been discussed in many forums. Sustainability is part and parcel of that concept. Today’s key materials provision, materials processing and materials application sustainability issues can be seen in the example of personal mobility applications.There are four significant elements in the system chain: (1) renewable energy conversion, (2) flexible power plants to level the time dependence of the electric power supply, (3) sharing energy using electric grids, and (4) handling the major challenge of energy storage on various time scales. In all cases, materials play an important role, and materials modelling using computer simulation has the potential to enhance system efficiency as well as operation lifetime.<br
Keywords: Renewable energy conversion; electric power supply; electric grids; energy storage; materials Innovation; sustainability